Impact of Subclinical and Clinical Kidney Allograft Rejection Within 1 Year Posttransplantation Among Compatible Transplant With Steroid Withdrawal Protocol - Owoyemi, Itunu (Transplant Direct, 2021)
Early acute kidney rejection remains an important clinical issue. METHODS. The current study included 552 recipients who had 1–2 surveillance or indication biopsy within the 1 y posttransplant. We evaluated the impact of type of allograft inflammation on allograft outcome. They were divided into 5 groups: no inflammation (NI: 95), subclinical inflammation (SCI: 244), subclinical T cell–mediated rejection (TCMR) (SC-TCMR: 110), clinical TCMR (C-TCMR: 83), and antibody-mediated rejection (AMR: 20). Estimated glomerular filtration rate (eGFR) over time using linear mixed model, cumulative chronic allograft scores/interstitial fibrosis and tubular atrophy (IFTA) ≥2 at 12 mo, and survival estimates were compared between groups. RESULTS. The common types of rejections were C-TCMR (15%), SC-TCMR (19.9%), and AMR (3.6%) of patients. Eighteen of 20 patients with AMR had mixed rejection with TCMR. Key findings were as follows: (i) posttransplant renal function: eGFR was lower for patients with C-TCMR and AMR (P < 0.0001) compared with NI, SCI, and SC-TCMR groups. There was an increase in delta-creatinine from 3 to 12 mo and cumulative allograft chronicity scores at 12 mo (P < 0.001) according to the type of allograft inflammation. (ii) Allograft histology: the odds of IFTA ≥2 was higher for SC-TCMR (3.7 [1.3-10.4]; P = 0.04) but was not significant for C-TCMR (3.1 [1.0-9.4]; P = 0.26), and AMR (2.5 [0.5-12.8]; P = 0.84) compared with NI group, and (iii) graft loss: C-TCMR accounted for the largest number of graft losses and impending graft losses on long-term follow-up. Graft loss among patient with AMR was numerically higher but was not statistically significant. CONCLUSIONS. The type of kidney allograft inflammation predicted posttransplant eGFR, cumulative chronic allograft score/IFTA ≥2 at 12 mo, and graft loss.